Hormonal Therapies for Acne: A Comprehensive Update for Dermatologists - Courtney A. Smith; Emily Gosnell; Turkan Banu Karatas; Chelsea Deitelzweig; Elizabeth M. B. Collins; Howa Yeung (Dermatology and Therapy)
Abstract Introduction Acne impairs quality of life, often leads to permanent scars, and causes psychological distress. This review aims to update dermatologists on the Federal Drug Administration (FDA)-approved and off-label use of combined oral contraceptives (COC), clascoterone, spironolactone, and emerging hormonal therapies for acne treatment. Methods We reviewed current literature on hormonal acne treatments and discussed common patient concerns, barriers to care, and individualized care needs. Results Different brands and dosings of COC have generally similar efficacy in treating acne. Dermatologists should discuss contraceptive options and provide individualized shared decision-making with patients based on patient preferences, contraceptive needs, comorbidity profile, access, and cost. Spironolactone is an effective acne treatment with clinical trial data to support its use as a first-line acne treatment for women with acne. Potassium monitoring is of low value for patients on spironolactone unless patients have specific risk factors for hyperkalemia. Clascoterone is a safe and effective topical anti-androgen for the treatment of acne in men and women with limited systemic effects on reproductive hormones. Conclusion Hormonal therapies are essential strategies to treat acne. Clinicians should expand the use of existing and emerging hormone therapy as part of their acne treatment strategies.